Functional Invariant Natural Killer T Cells Secreting Cytokines Are Associated With Non-Progressive Human Immunodeficiency Virus-1 Infection but Not With Suppressive Anti-Retroviral Treatment - Singh, Dharmendra; Ghate, Manisha; Godbole, Sheela; Kulkarni, Smita; Thakar, Madhuri (Frontiers in Immunology, 2018)
Background: CD1d restricted Invariant natural killer T (iNKT) cells are important in the activation and regulation of immune responses. Limited information is available regarding the functional role of iNKT cells in the HIV disease progression. Methodology: α-GalCer stimulated iNKT cells were characterized for their functionality in terms of cytokine production (IFN-γ, TNF-α, IL-2, IL-4 and IL-21) and CD107a expression in HIV-1 infected [23 long term non progressors (LTNPs), 28 progressors, 18 patients before and after suppressive Anti-Retroviral Treatment (ART)] along with 25 HIV-1 negative subjects using multicolor flowcytometry. Results: The functional profile of α-GalCer stimulated iNKT cells was similar in LTNPs and healthy controls. The number of LTNPs showing functional response in terms of secretion of cytokines (IFN-γ/IL2/TNF-α) and CD107a expression was significantly higher than seen in the progressors. The cytokine secretion by the stimulated iNKT cells was predominantly Th1 type. The frequencies of iNKT cells showing secretion of IFN-γ or IL2 or TNF-α or expression of CD107a were higher in LTNPs (p<0.05 for all) and also significantly associated with lower plasma viral load (p value ranged from 0.04 to 0.003) and higher CD4 count (p value ranged from 0.02 to <0.0001). The functional profile of the iNKT cells before and after ART did not differ significantly indicating absence of restoration of iNKT cells functionality after suppressive ART. The IL-4 and IL-21 secreting iNKT cells were rare in all study populations. Conclusion: The presence of functional iNKT cells secreting number of cytokines in non-progressive HIV infection could be one of the multiple factors required to achieve HIV control and hence have relevance in understanding the immunity in HIV infection. The failure of restoration of the iNKT functionality after ART should be potential area of future research.